2021
DOI: 10.1111/joa.13457
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐CT of the human ossicular chain: Statistical shape modeling and implications for otologic surgery

Abstract: The ossicular chain is a middle ear structure consisting of the small incus, malleus and stapes bones, which transmit tympanic membrane vibrations caused by sound to the inner ear. Despite being shown to be highly variable in shape, there are very few morphological studies of the ossicles. The objective of this study was to use a large sample of cadaveric ossicles to create a set of three‐dimensional models and study their statistical variance. Thirty‐three cadaveric temporal bone samples were scanned using mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The accuracy of this pipeline is further corroborated by comparing its findings to published findings of manual measurements of similar metrics. Reported anatomical measurements for malleus manubrium length, 6,11‐13 incus interprocess angle, 13 facial nerve first and second genu angles, 14‐16 facial nerve–cochlea distance, 17 and superior EAC‐tegmen distance 18 in this study have been consistent with measurements reported in previous literature. However, our methodology for calculating incus short and long process lengths varies from previous definitions.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The accuracy of this pipeline is further corroborated by comparing its findings to published findings of manual measurements of similar metrics. Reported anatomical measurements for malleus manubrium length, 6,11‐13 incus interprocess angle, 13 facial nerve first and second genu angles, 14‐16 facial nerve–cochlea distance, 17 and superior EAC‐tegmen distance 18 in this study have been consistent with measurements reported in previous literature. However, our methodology for calculating incus short and long process lengths varies from previous definitions.…”
Section: Discussionsupporting
confidence: 90%
“…This is the first study, to our knowledge, to validate a method for automated anatomical measurement extraction with reliable accuracy. Prior methods for calculating clinically relevant anatomical measurements typically involve manual segmentation of structures on CT imaging with placement of fiducials on visualization software [6][7][8] or meticulous harvesting of cadaveric structures with direct manual measurements. [9][10][11] By manually segmenting a single average bone template along with clinical relevant landmarks, this image registration-based method is able to automatically propagate template labels to other temporal bone scans with reliable accuracy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The temporal bone and lateral skull base contain a complex three-dimensional (3D) geometry of nerves, arteries, veins, as well as the organs for both hearing and balance (1). Due to this complex anatomy, multiple efforts over the years have aimed at defining the anatomical norms and variations of specific temporal bone structures, such as the ossicles, sigmoid sinus, and cochlea (2)(3)(4). These efforts have sought to better understand surgical landmarks and to investigate the biological significance of these anatomical variations.…”
Section: Introductionmentioning
confidence: 99%
“…By understanding the way shapes vary and whether separate cohorts vary differently, subtle changes can be uncovered. This technique has been used to quantify the variability in boney and soft tissue structures such as the lumbar spine, hip, knee, ankle, orbit, ossicles and levator ani (Bartling et al, 2021 ; Gass et al, 2022 ; Pavlova et al, 2017 ; Vafaeian et al, 2022 ; Vrancken et al, 2014 ). However, SSM has not been used to examine a hollow cavity such as the oropharynx in vivo.…”
Section: Introductionmentioning
confidence: 99%